Effect of whitening dentifrices on the surface roughness of a nanohybrid composite resin - da Rosa, Gabriela Migliorin; da Silva, Luciana Mendonça; de Menezes, Márcio; do Vale, Hugo Felipe; Regalado, Diego Ferreira; Pontes, Danielson Guedes (European Journal of Dentistry, 2016)
Objectives: The present study verified the influence of whitening dentifrices on the surface roughness of a nanohybrid composite resin. Materials and Methods: Thirty-two specimens were prepared with Filtek™ Z350 XT (3M/ESPE) and randomly divided into four groups (n = 08) that were subjected to brushing simulation equivalent to the period of 1 month. The groups assessed were a control group with distilled water (G1), Colgate Total 12 Professional Clean (G2), Sensodyne Extra Whitener Extra Fresh (G3), and Colgate Luminous White (G4). A sequence of 90 cycles was performed for all the samples. The initial roughness of each group was analyzed by the Surface Roughness Tester (TR 200-TIME Group Inc., CA, USA). After the brushing period, the final roughness was measured, and the results were statistically analyzed using nonparametric Kruskal–Wallis and Dunn tests for intergroup roughness comparison in the time factor. For intragroup and “Δ Final − Initial” comparisons, the Wilcoxon test and (one-way) ANOVA were, respectively, performed (α = 0.05). Results: The roughness mean values before and after brushing showed no statistically significant difference when the different dentifrices were used. None of the dentifrices analyzed increased significantly the nanohybrid composite resin surface roughness in a 1 month of tooth brushing simulation. Conclusions: These results suggest that no hazardous effect on the roughness of nanohybrid composite resin can be expected when whitening dentifrices are used for a short period. Similar studies should be conducted to analyze other esthetic composite materials.
Keywords: Composite resin; roughness; tooth brushing; whitening dentifrices